THE EFFECTS OF THE RETROSPECTIVE MEASURES IN THE RENEWABLE ENERGY SECTOR: THE EFFECTS OF THE RETROSPECTIVE MEASURES IN THE RENEWABLE ENERGY SECTOR - Nikolova , Ralitsa (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The boom in investments in the renewable energy sector in the recent years has prompted many EU countries to implement retrospective measures in the form of legislative changes that have become one of the main risks facing the development of renewable technologies. This article examines the main effects of the retrospective measures. Among them are the more difficult access and higher cost of financing, reducing the cost effectiveness of the renewable energy projects and the reduction of investments in this sector.